Quality of life in juvenile arthritis adolescents studying at school or at home - Tatyana Andreevna Shelepina (Современная ревматология)
The data of a number of questionnaires were used to analyze quality of life (QL) in juvenile arthritis adolescents studying at school versus at home. A group of those who studied at home included patients with clear medical indications for this education form and those who optionally chose this education. According to a number of indicators, QL proved to be lower in the group of patients studying at home who had no clear medical indications.